Golexanolone affords sustained microglia and astrocytes activation improvement in a rat model of Parkinson’s disease - Mincheva, Gergana; Pedrosa, Maria A.; Martínez-García Vázquez, Mar; Vazquez, Lola; Blackburn, Thomas P.; Doverskog, Magnus; Llansola, Marta; Felipo, Vicente (Frontiers in Immunology, 2025)
IntroductionGolexanolone improves motor and non-motor alterations in the unilateral 6-OHDA rat model of PD. We hypothesized that a key mechanism by which golexanolone induces these beneficial effects is by reducing microglia activation, thus reducing pro-inflammatory factors (TNFα, IL-1α, HMGB1) which activate astrocytes. This work aims were to assess if golexanolone affords sustained improvement of glial activation and pro-inflammatory factors at 3 and 9 weeks after 6-OHDA injection.Results6-OHDA rats show pro-inflammatory microglia in SN and striatum, with reduced area and increased TNFα at 3 and 9 weeks, increased TNFα, IL-1α and HMGB1 and pro-inflammatory A1 astrocytes activation with increased GFAP, vimentin and S100B and reduced S100A10. Golexanolone reversed microglia activation, the increase in pro-inflammatory factors and astrocytes A1 activation both at 3 and 9 weeks. Golexanolone reversed microglia activation, the increase in pro-inflammatory factors and astrocytes A1 activation both at 3 and 9 weeks.DiscussionSustained improvement of glial activation in SN and striatum would be a key mechanism in the improvement of PD symptoms by golexanolone.